Peningkatan Penjualan Produk Pangan Kelompok Tani Kancil Putih melalui Media E-Commerce - Nancy Eka Putri Manurung; Ahlam Inayatullah; Raudhatus Sa’adah (Jurnal Nusantara Mengabdi, 2023)
Purpose: This community service activity is aimed to increasing sales of food products through e-commerce platforms which will expand the marketing network and increase groups income. Methodology: This community service activity was done at Kelompok Tani Mandiri, Subdistrict Ilir Barat. These activities carried out through several stages. First, preparation, dan second step was implementation. Participants were socialized and invited to create social own media accounts and made design promotion using canva. Then all of participants were accompanied as the implementatio of socialization. The last step of community service activity was evaluation of program. Results: Participant knew that sales through online media have more advantages than offline media, by using e-commerce. Participants have own social media and could make promotion using graphic design by canva then upload those promotion using their social media. Conclusion: marketplace was one way that could help increased the marketing of service participants by disseminating sales information through social media accounts.